Swimming and peak bone mineral density: A systematic review and meta-analysis - Gomez-Bruton, A.; Montero-Marin, J.; González-Agüero, A.; Gómez-Cabello, A.; Garcia-Campayo, J.; Moreno, L. A.; Casajús, J. A.; Vicente-Rodriguez, G. (Journal of Sports Sciences, 2018)
This meta-analysis aims to determine the effects of regular swimming on bone mineral density (BMD) in young adults (18-30 years). A systematic search was performed in Pubmed, SPORTDiscus and the Cochrane Library from the earliest possible year to March 2016. Swimmers were compared to non-athletic controls (CG) and to high-impact athletes (HIGH). Effect sizes with the Hedges g in random effects models were developed. Fourteen studies met the inclusion criteria and were included in the meta-analyses. Swimmers presented similar BMD values to CG in whole-body (g = -0.20; P = 0.251), femoral neck (g = -0.05; P = 0.818) and lumbar spine (g = 0.18; P = 0.492); and lower BMD in the whole-body (g = -1.21; P < 0.001), femoral neck (g = -1.51; P < 0.001) and lumbar spine (g = -0.84; P = 0.017) than the HIGH. For the whole-body differences, the higher the latitude the smaller the differences between swimmers and HIGH (B = 0.10; P = 0.001). For the femoral neck differences, age also seemed to reduce the differences between groups (B = 0.19; P = 0.020). Young adult swimmers present similar BMD values than CG and lower values than HIGH.